Combined QM/MM investigation on the light-driven electron-induced repair of the (6-4) thymine dimer catalyzed by DNA photolyase - Faraji, Shirin; Dreuw, Andreas (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2013)
The (6-4) photolyases are blue-light-activated enzymes that selectively bind to DNA and initiate splitting of mutagenic thymine (6-4) thymine photoproducts (T(6-4)T-PP) via photoinduced electron transfer from flavin adenine dinucleotide anion (FADH-) to the lesion triggering repair. In the present work, the repair mechanism after the initial electron transfer and the effect of the protein/DNA environment are investigated theoretically by means of hybrid quantum mechanical/molecular mechanical (QM/MM) simulations using X-ray structure of the enzyme-DNA complex. By comparison of three previously proposed repair mechanisms, we found that the lowest activation free energy is required for the pathway in which the key step governing the repair photocycle is electron transfer coupled with the proton transfer from the protonated histidine, His365, to the N3′ nitrogen of the pyrimidone thymine.
Gesehen am 18.12.2017